Emergence and Diversity of Modern Human Behavior in Paleolithic Asia - Kaifu, Yōsuke, 1969- (Book collections on Project MUSE., 2014)
Despite the obvious geographic importance of eastern Asia in human migration, its discussion in the context of the emergence and dispersal of modern humans has been rare. Emergence and Diversity of Modern Human Behavior in Paleolithic Asia focuses long-overdue scholarly attention on this under-studied area of the world. Arising from a 2011 symposium sponsored by the National Museum of Nature and Science in Tokyo, this book gathers the work of archaeologists from the Pacific Rim of Asia, Australia, and North America, to address the relative lack of attention given to the emergence of modern hum.